CFD Analysis of lab-scale prototypes two-phase fluid flow twin-scroll compressor and expander - Lyu, Wenjing; Luzi, Giovanni; Delgado, Antonio; Schellin, Thomas E. (Energy, 2025)
Computational Fluid Dynamics is a crucial tool for designing Positive Displacement machines. In this regard, we have developed a Computational Fluid Dynamics in-house solver to predict phase change phenomena inside the chambers of twin-scroll compressors and expanders handling two-phase fluid flow. The main numerical assessments of this work include velocity and pressure distribution, average inlet and outlet mass flow rates, vapor condensation and liquid evaporation phenomena, as well as isentropic, adiabatic, and volumetric efficiencies. These are essential for determining whether the machines experience excessive vibrations or work under overloaded conditions. The numerical results obtained with our solver align well with those obtained with a Deterministic Model found in existing literature. Additionally, the pressure and velocity distribution inside the scroll machines are similar to those reported in numerical studies of single-phase flow scroll compressors and expanders available in the literature.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Adiabatic efficiency; Dynamic mesh solver; Isentropic efficiency; Twin-scroll machines; Two-phase flow; Volumetric efficiency